Pengembangan Instrumen Soal Higher Order Thingking Skill (HOTS) pada Tema 4 Subtema 3 di Kelas V SD Negeri 2 Selakau - Julayka Julayka; Kartono Kartono; Hamdani Hamdani (Departement of Mathematics Education, 2024)
This research aims to develop and produce a feasible Higher Order Thinking Skills (HOTS) test instrument. This is a developmental research adapted from the Borg & Gall development model, which includes 7 development steps as follows: research and information collecting, planning, develop preliminary form a product, preliminary field testing, main product revision, field testing, and operational product revision. The data sources for this research were 30 students from SD Negeri 2 Selakau. The data collection instruments in this research consisted of interviews, questionnaires, and the HOTS test results. The data analysis techniques used in this research were the validation analysis of the questions from the aspects of Material, Construction, and Language, as well as the item analysis of HOTS questions. The research results showed that the HOTS test instrument, which consisted of 7 essay questions, obtained an average validity score of 93% in the material aspect, 96% in the construction aspect, and 93% in the language aspect. The instrument, consisting of 7 questions, was deemed valid with a reliability degree of 0.722 (high) and the difficulty level and discriminative power of the questions corresponded to the characteristics of HOTS questions. Thus, the product in the form of the HOTS Test Instrument is declared feasible for use.